Where boys don't dance, but women still thrive: using a development approach as a means of reconciling the right to health with the legitimization of cultural practices - Melisa Demir; Bilkis Vissandjée; Danielle Jacobson; Gillian Einstein (BMC, 2020)
Abstract Human rights language has become a common method of internationally denouncing violent, discriminatory or otherwise harmful practices, notably by framing them as reprehensible violations of those fundamental rights we obtain by virtue of being human. While often effective, such women's rights discourse becomes delicate when used to challenge practices, which are of important cultural significance to the communities in which they are practiced. This paper analyses human rights language to challenge the gender disparity in access to health care and in overall health outcomes in certain countries where such disparities are influenced by important cultural values and practices. This paper will provide selected examples of machismo and marianismo discourses in certain Latin American countries on the one hand and of female genital cutting/excision (FGC/E) in practicing countries, both of which exposed to women's rights language, notably for causing violations of women's right to health. In essence, a reflective exercise is provided here with the argument that framing such discourses and practices as women's rights violations. Calling for their abandonment have shown that it may not only be ineffective nor at times appropriate, it also risks delegitimizing associated discourses, norms and practices thereby enhancing criticisms of the women's rights movement rather than adopting its principles. A sensitive community-based collaborative approach aimed at understanding and building cultural discourses to one, which promotes women's capabilities and health, is proposed as a more effective means at bridging cultural and gender gaps.